2006
DOI: 10.1259/dmfr/22989395
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of surface and volume rendering in 3D-CT of facial fractures

Abstract: SR provided sufficient and time efficient means for 3D-visualization of facial fractures in this study. No diagnostic benefit of VR over SR was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…4,[12][13][14] In all children, we found that 2D+3D CT increased the sensitivity (81.3%, p < 0.05) when compared with 2D CT only (74.5%) in the diagnosis of linear skull fractures. In addition, fewer false-negative calls (or undercalls) with 2D+3D (n = 45) when compared with 2D alone (n = 65) showed statistical significance (p < 0.05).…”
Section: Discussionmentioning
confidence: 74%
“…4,[12][13][14] In all children, we found that 2D+3D CT increased the sensitivity (81.3%, p < 0.05) when compared with 2D CT only (74.5%) in the diagnosis of linear skull fractures. In addition, fewer false-negative calls (or undercalls) with 2D+3D (n = 45) when compared with 2D alone (n = 65) showed statistical significance (p < 0.05).…”
Section: Discussionmentioning
confidence: 74%
“…Several studies evaluated SSD and VR with regard to fracture detection [19][20][21], revealing only minor differences in fracture detection between these two algorithms [20]. As opposed to SSD, VR also offers the ability to show subcortical abnormalities [20,22] and does not require additional postprocessing time to remove possible beam-hardening artefacts at the level of the skull base [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, these programs use different reconstruction algorithms and/or methods of measurement ultimately intended to aid professionals in formulating more accurate maxillofacial diagnosis and treatment plans. The reconstruction pattern may be determined by surface rendering or volumetric rendering as previously investigated, 10,24 although the evaluation of patterns of linear measurement remains unclear.…”
Section: -17mentioning
confidence: 99%